The Role of Green Accounting in Enhancing Sustainability Report Integrity - Lenny Dermawan Sembiring; Ratih Puspitasari; Umi Mas'ulah; Ngurah Pandji Mertha Agung Durya; Murwani Wulansari (LPPPIPublishing, 2026)
The purpose of this study is to explain the role of green accounting in enhancing sustainability report integrity. This study uses a qualitative and descriptive approach to explain the role of green accounting in enhancing sustainability report integrity. The use of a qualitative and descriptive approach is supported by secondary data such as books, national and international journal articles, and related sources. The research results show that green accounting plays a crucial role in maintaining and enhancing the integrity of a company's sustainability report. Through the implementation of green accounting, sustainability reports are no longer merely public relations documents but are transformed into honest, transparent, and accountable strategic documents. The primary role of green accounting in strengthening report integrity is transforming qualitative data into accurate quantitative data, standardization and transparency of environmental costs, helps meet global standards, facilitates third-party auditing, and reduces greenwashing practices.